2012
DOI: 10.4103/0971-9261.102329
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected invasive neonatal gastrointestinal mucormycosis: A clinicopathological study of six cases from a tertiary care hospital

Abstract: Aim:To analyse the clinicopathological features of neonatal mucormycosisMaterials and Methods:Retrospective analysis of cases of neonatal gastrointestinal mucormycosis.Results:There were six neonates with male: female ratio of 1:1. Except one all were preterm babies. The clinical presentation was abdominal distension in the majority. All were clinically diagnosed as either NEC or toxic megacolon with perforation. Neonatal gastrointestinal mucormycosis was not suspected clinically in any. All the children were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…However, on the basis of data available from certain groups of patients, the disease prevalence appears to be nearly 0.16% amongst diabetics and 1.2% amongst renal transplant recipients, with most of these cases manifesting as the ROC form . Also, gastrointestinal mucormycosis reportedly occurs in nearly 20% of all operated cases of neonatal enterocolitis in one center . In fact, the frequency of gastrointestinal mucormycosis was found to be so high in that centre that clinicians suspect the disease in any neonate having intestinal perforation.…”
Section: High Incidencementioning
confidence: 99%
“…However, on the basis of data available from certain groups of patients, the disease prevalence appears to be nearly 0.16% amongst diabetics and 1.2% amongst renal transplant recipients, with most of these cases manifesting as the ROC form . Also, gastrointestinal mucormycosis reportedly occurs in nearly 20% of all operated cases of neonatal enterocolitis in one center . In fact, the frequency of gastrointestinal mucormycosis was found to be so high in that centre that clinicians suspect the disease in any neonate having intestinal perforation.…”
Section: High Incidencementioning
confidence: 99%
“…The other predisposing factors are preterm baby, steroid therapy, malnutrition, immunosuppression, low birth weight, immature immune system of the neonate with fragile skin barrier, orogastric intubation. (1,5,6,7,8) Members of mucoraceae show affinity for arterial invasion leading to thrombosis and ischaemic infarction of the tissue supplied by the artery. In gastrointestinal mucormycosis, this leads to gangrene of the involved bowel segment mimicking NEC (Necrotising Enterocolitis).…”
Section: Discussionmentioning
confidence: 99%
“…Since its first review in 1994, about 30 cases of neonatal GIM have been reported in English literature till date [1,3]. Of these, 22 are from India [1,[3][4][5].…”
Section: Discussionmentioning
confidence: 99%